Science behind the socket-shield technique: analytical literature review - Farhat, Chantal Cherine Clémence (2023)
Introduction: Preserving the periodontal apparatus was a growing concept to save the buccal bone through protecting the blood supply to the area. However, tooth loss is inevitable and so is buccal bone dimensional changes. Here came the partial extraction therapies to better manage the devastating functional and esthetic consequences of tooth extraction. Objectives: Thirteen years have passed since socket-shield technique, the most recent among those therapies, had been introduced to the spectrum of implant dentistry. Science behind, evidence of the technique, advantages and disadvantages, complications, technique modifications and long-term follow up are being introduced to the bulk of knowledge with time. The aim of this dissertation is to illustrate as clearly as possible, but also to evaluate, the utmost available information about socket-shield technique through a literature review. Material and methods: Through a bibliographic search conducted on PubMed database , Web of Science, and Google Schola, we have selected a total of 34 articles over 288 positive results. The included articles are published between January 1990 and February 2020. A descriptive and analytical study of the data is carried out to examines the available evidence regarding the partial extraction and especially the socket-shield technique. Results: Socket-Shield Technique showed great performance regarding esthetics and function, but, many technical limitations not be ignored, were extracted from the articles , leading to absolutely end up in failures at different aspects whether technical, functional, or esthetical, ; the results of the bibliographic review point also on the very limited follow-up periods come that with the case reports and series, that form in fact the majority of the bulk of knowledge about SST, and they are considered untrustworthy to predict the long-term prognosis of SST. Conclusions: In conclusion, although it is evident that a great consensus about the clinical and esthetic success of SST has been earned, there is a greater unanimity among authors that the aforementioned technique still requires long-term clinical follow-up.